Perancangan Interior Offline Store Penyewaan Produk Fashion Ready-to-Wear Dresscodes di Surabaya - Catherina Putri; Sriti Mayang Sari; Linggajaya Suryanata (Intra, 2019)
In the midst of the increasingly high outfit needs for special events at affordable prices, there is a business concept of online designer dresses rentals. One of the pioneers in this business was Dresscodes. The idea of the design came from the owner's desire to develop Dresscodes’ retail business by opening an offline store in Surabaya, as one of the largest cities in Indonesia with a rapidly growing interest in fashion.The purpose of the offline store interior design of Dresscodes ready-to-wear fashion products rental in Surabaya is to provide the customers to see and check fashion product collections directly, a space design that can accommodate various activities, and present a visually interesting space experience for the users. The concept